Retrospective evaluation of dento-alveolar morphology after fixed orthodontic treatment at HUSM: laser scanning 3D model - Massoud, Moustafa Mahmoud Hassaballa (2017)
The purpose of this study was to evaluate the validity and reliability of orthodontic measurements made on laser scanned 3D models created with NextEngine laser scanner and ScanStudioHD software and to evaluate arch dimensional changes in subjects treated with extraction and non-extraction after conventional orthodontic treatment using laser scanned 3D models. Dental models of 104 patients (416 dental models) were randomly selected from the archives of School of Dental Sciences, Universiti Sains Malaysia. Scanning, imaging and measuring were completed to achieve objectives. A total of 100 set were measured by Mitutoyo digital caliper (DC) and ScanStudio HD software to achieve first objective and 416 dental models were used to achieve the second objective. Statistical comparisons were performed using paired t-test, independent t-test and RM ANCOVA. The validity (accuracy) of the digital measurements showed no statistical differences in any of the measurements performed. The reliability coefficient values were comparable between laser scanned 3D models and measurements using DC and the values of coefficient were in the range of strong correlation. The results showed that linear measurements of dental models using laser scanned 3D models are valid and reliable and can be used for various clinical orthodontic procedures. Significant differences were found in pre-treatment groups for 1-PMD and LII in maxillary arch whereas there were significant changes in all parameters except for ICD, 1-PMD, LII and OB in post-treatment group. Significant differences were observed in all parameters except for ICD and 1-PMD in XLA group. In non-extraction group, significant changes were observed in all parameters except in IMD, MCF and OJ. There were significant changes in all parameters of mandibular arch except for ICD, 1- PMD and A/L in pretreatment group whereas there were significant changes in all parameters except for ICD, 1-PMD and LII in post-treatment group. For pre and posttreatment differences, the changes of mandibular dental arch were significant in all variables except A/P in non-extraction group whereas all parameters except for 2-PMD, IMD and MCF were changed significantly in extraction group. The results of the present study showed conventional orthodontic treatment with extraction and non-extraction pattern potentially producing statistically significant changes of the dental arches. Thus, this finding would be beneficial for orthodontic patients at Hospital Universiti Sains Malaysia (HUSM) as 3D record for comprehensive diagnosis and consequently successful orthodontic treatment planning.